ナンキョク オングルトウ サン ドジョウ ソウルイ モクロク - 秋山, 優; アキヤマ, マサル; AKIYAMA, Masaru (国立極地研究所, 1968)
P(論文) A list of terrestrial and subterranean micro algae recognized on the Ongul Islands, Antarctica is given. In the list are enumerated twenty-eight genera and thirty-two species of algae including sixteen species of Chlorophyceae, four species of Xanthophyceae, three species of Bacillariophyceae and nine species of Cyanophyceae. Of these algae, the following species are new to the Antarctica Chlamydomonas agloeformis PASCHER, Carferia simplex PASCHER, Stichococcus exiguus GERN., Pseudo-Pleurococcus printzii VISCHER, Bracteacoccus irregularis (PETERSEN) STARR, Kentrosphaera bristolae G. M. SMITH, Dictyosphaerium elegans BACHMANN, Cosmarium cucurubita BREB. forma rotundatum KRIEG., Monodus subterraneus PETERSEN, Botrydiopsis arhiza BORZI, Bumilleria exillis KLEBS, Monocilia viridis GERN., Tolypothrix bouteillei (BREB. et DESM.) FORTI and T. fragilis (GARDN.) GEITLER. departmental bulletin paper